2016
DOI: 10.1021/acssuschemeng.6b01965
|View full text |Cite
|
Sign up to set email alerts
|

Green Recovery of Rare Earths from Waste Cathode Ray Tube Phosphors: Oxidative Leaching and Kinetic Aspects

Abstract: In this work, we developed a green and efficient process for the recovery of rare earths from waste cathode ray tube phosphors. The mixture of hydrochloric acid and hydrogen peroxide was identified as the most suitable leaching agent due to the synergistic effect. The effects of various parameters on leaching process were explored, and the optimal conditions with stirring speed 600 rpm, temperature 313 K, 1 M of H2O2, 4 M of HCl, and leaching time of 90 min were determined. Furthermore, a possible reaction mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Therefore, it is often mixed with cheaper yttrium-containing mischmetal or with HREEs. For this reason, magnesium alloys are very interesting from the point of view of consuming the excess of yttrium that will become available from the recycling of lamp phosphors from end-of-life fluorescent lamps [88,[121][122][123][124] and from CRT phosphor waste [88,[125][126][127][128]. It can also be used to consume most of the REEs that are available in excess (La, Ce, Sm, Gd, Ho, Er, Tm), thereby balancing their markets as well.…”
Section: Magnesium and Aluminum Alloys As A Possible Solution To The mentioning
confidence: 99%
“…Therefore, it is often mixed with cheaper yttrium-containing mischmetal or with HREEs. For this reason, magnesium alloys are very interesting from the point of view of consuming the excess of yttrium that will become available from the recycling of lamp phosphors from end-of-life fluorescent lamps [88,[121][122][123][124] and from CRT phosphor waste [88,[125][126][127][128]. It can also be used to consume most of the REEs that are available in excess (La, Ce, Sm, Gd, Ho, Er, Tm), thereby balancing their markets as well.…”
Section: Magnesium and Aluminum Alloys As A Possible Solution To The mentioning
confidence: 99%
“…Fig3 showed the systematic two step leaching process of waste fluorescent powder [10], here it is reported that during 1 st step the leach liquor contains a higher percentage of Y and Eu and 2 nd step leach liquor is reached in Ce and Tb metal. Different researcher studied the differentleaching agent for recycling of REMs such as Eu and Y from CRT waste [24,53,54,55,56,57].…”
Section: Dual Acid Leachingmentioning
confidence: 99%
“…Hydrometallurgical method has some advantages over pyrometallurgical one, such as lower energy consumption, lower toxic gas emission, and more effective leaching of metals . The conventional hydrometallurgical process for REEs recovery uses various types of mineral acids as leaching agents, such as hydrochloric acid (HCl), sulfuric acid (H 2 SO 4 ), and nitric acid (HNO 3 ) . Review literatures of acid extraction of Y and Eu revealed that high temperature, long reaction time, and concentrated acid are needed in leaching …”
Section: Introductionmentioning
confidence: 99%
“…5 The conventional hydrometallurgical process for REEs recovery uses various types of mineral acids as leaching agents, such as hydrochloric acid (HCl), sulfuric acid (H 2 SO 4 ), and nitric acid (HNO 3 ). 6,17,18 Review literatures of acid extraction of Y and Eu revealed that high temperature, long reaction time, and concentrated acid are needed in leaching. [19][20][21] 3860 www.soci.org J Lie, S Ismadji, J-C Liu…”
Section: Introductionmentioning
confidence: 99%